Support mechanisms for renewables: How risk exposure influences investment incentives - Lena Kitzing; Christoph Weber (University of Duisburg-Essen, Chair for Management Science and Energy Economics, 2014)
We analyse quantitatively how risk exposure from different support mechanisms, such as feed-in tariffs and premiums, can influence the investment incentives for private investors. We develop a net cash flow approach that takes systematic and unsystematic risks into account through cost of capital and the Capital Asset Pricing Model as well as through active liquidity management. Applying the model to a specific case, a German offshore wind park, we find that the support levels required to give adequate investment incentives are for a feed-in tariff scheme approximately 5-7% lower than for a feed-in premium scheme. The effect of differences in risk exposure from the support schemes is significant and cannot be neglected in policy making, especially when deciding between support instruments or when determining adequate support levels.
Keywords: 330; investment risk; support policies; unsystematic risk; liquidity management; offshore wind; feed-in tariffs